2021
DOI: 10.3389/fcvm.2021.675202
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myosarcoma in a Newborn Infant—A Case Report and Literature Review

Abstract: Background: Malignant cardiac neoplasms are extremely rare in neonates. Prenatal diagnosis is often not available. Initial symptoms can mimic non-cardiac diseases. We present a pre-mature newborn, birth-weight 2,480 g, 34 gestational weeks, which underwent cardiac surgery due to a cardiac tumor.Case Summary: This was a 3–rd pregnancy after two spontaneous abortions to a mother with thrombophilia, diabetes, hydramnios, and retroplacental hematoma. The baby was admitted to NICU with transitory respiratory failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Currently, no studies have shown a correlation between sarcoma and GDM. A case report indicated that an infant whose mother had diabetes had inborn cardiac sarcomas ( 27 ). Although there is a lack of evidence, it undoubtedly further suggests that maternal GDM may have harmful effects on embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no studies have shown a correlation between sarcoma and GDM. A case report indicated that an infant whose mother had diabetes had inborn cardiac sarcomas ( 27 ). Although there is a lack of evidence, it undoubtedly further suggests that maternal GDM may have harmful effects on embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some ethnic variability, as more cases are found in White and Hispanic races compared to African and Asian [7]. It mainly affects younger age groups with a male predilection, although it can affect subjects of a wide range of ages, from those in the neonatal period to the elderly [7][8]. Immunology, inflammatory markers, and cytokines also play an important role in the initiation and progression of this disease [9][10].…”
Section: Discussionmentioning
confidence: 99%